Physico-mechanical properties of kedondong (Canarium spp.) and batai [Paraserianthes falcataria (L.) Nielsen] impregnated with phenolic resin and their relations to sorption behaviour - Boneka, Arfah Shawati (2022)
Kedondong (Canarium spp.) and batai (Paraserianthes falcataria (L.) Nielsen) hardwood were chosen as the raw materials to improve their dimensional stability and mechanical performances via several scientific treatments that this study undertook. Wood modifications of these two species were conducted with the objective to enhance their low dimensional instability, inferior mechanical strength and high hygroscopicity which limit their commercial utilization. In this study, kedondong and batai samples were impregnated with low-molecular weight phenol formaldehyde (LMwPF) resin at 15%, 20% and 30% concentrations followed by the curing process at 150 °C for 60 minutes. Weight percent gain (WPG), surface wettability and physical properties like water absorption (WA), thickness swelling (TS), swelling coefficient (SC) and anti-shrink efficiency (ASE) were all monitored by this study. In addition, mechanical strength in terms of their bending and hardness strengths and sorption behaviour of untreated sample against impregnated samples were also individually evaluated. Consequently, results showed that impregnated batai demonstrated better treatability than the kedondong sample. However, impregnated kedondong showed an increase in WPG as the LMwPF resin concentration increased from 15% to 30%. Surface wettability of impregnated sample for both species showed distinct decrements compared to their untreated samples. The results also showed that the impregnated kedondong decreased significantly in terms of WA, TS and SC while the ASE increased with increment of resin concentration. This trend was similar for impregnated batai. In terms of its mechanical properties, the modulus of rupture (MOR) value of batai between the impregnated sample at 15% resin concentration and the untreated batai sample showed significant difference but there was no significant difference for the kedondong sample. Nevertheless, both the kedondong and batai species showed no significant difference in terms of modulus of elasticity (MOE) and hardness properties. The equilibrium moisture content (EMC) at 95% relative humidity (RH) of the untreated kedondong and batai samples records 19.10% and 21.19% respectively. Meanwhile, for the impregnated kedondong the EMC ranged from 18.14% to 18.43%, and for batai the EMC was recorded at 13.35% - 17.12%. Kedondong and batai samples shows a reduction in EMC up to 11.57% and 58.74% respectively after being impregnated with LMwPF resin. In addition, there was a noticeable difference in the hysteresis loop between the untreated and all impregnated samples for both species. The highest absolute hysteresis (AH) was marked at 80% RH with values at 3.74% and 3.85% for the untreated kedondong and batai, respectively. The AH also showed a marked reduction due to impregnation. Moreover, due to the penetration of LMwPF resins in wood cells, it had resulted the low hysteresis ratio (HR) when compared to the untreated samples. The projected-fibre saturation point (p-FSP) that was determined by applying the hailwood-horrobin (HH) Model for this study, showed that the impregnated kedondong and batai exhibited lower EMC compared to the untreated samples. Therefore, it could be concluded that the impregnation method with LMwPF resin increased the bending strength of batai, and enhanced the dimensional stability and reduced the hygroscopicity of kedondong and batai woods.